Reflection of Indonesian Educators on the Implementation of the Merdeka Curriculum - Rokayah, Rokayah; Hermita, Neni; Vebrianto, Rian; Mujtahid, Iqbal; Sulistiyo, Urip; Samsudin, Achmad (Universitas Pendidikan Indonesia, 2023)
Driven by a commitment to address challenges associated with the Merdeka Curriculum's implementation in Indonesia, this paper explores reflections and experiences of Indonesian educators. The researchers' anxiety, stemming from the need for effective application, underscores the study's motivation to enhance the educational experience for educators and students alike. Conducted through qualitative questionnaires and semi-structured interviews with fifteen participants, the research focuses on three reflective dimensions (in, on, and for) employing an exploratory case study design. In reflection-in-action, educators emphasize a shift towards student-centered learning, promoting active involvement, critical thinking, and self-directed learning. Reflection-on-action reveals educators perceiving the curriculum as highly interactive, but they acknowledged the need for patience and time in implementing significant changes, considering varying levels of receptivity among teaching staff. Reflection-for-action demonstrates educators actively evaluating the Merdeka Curriculum, employing strategies like fostering relationships and leveraging social media for knowledge sharing. Overall, the study highlighted the potential of the Merdeka Curriculum to enhance the overall quality of schools and contribute to the academic success of Indonesian students. The findings offer valuable insights for policymakers, curriculum developers, and educational practitioners seeking to refine the implementation process and enhance professional development programs. Ultimately, this research contributes to the ongoing efforts to empower educators and students and improve the effectiveness of education in Indonesia.